Malaysia Country Gender Note 2021 - World Bank (World Bank, Kuala Lumpur, 2021)
The Malaysia Country Gender Diagnostic Note will serve as a guide to identify the priority areas for the World Bank country office in Malaysia to address the gender equality challenges in meeting the country’s aspirations and next stage of development, particularly in the areas of inclusive growth and sustainability. This diagnostic builds on the first review that was completed in 2018, and aims to understand the changes from 2017 to 2020, especially with regards to the impact of the pandemic on gender issues. This note has strived to obtain the most current data. Where 2019 to 2020 micro-data is not available, this diagnostic is based on data and analysis drawn from published reports using data obtained from the Department of Statistics Malaysia. The diagnostic commences with a review of Malaysia’s performance in gender indicators in global indices, and documents areas of progress and areas where Malaysia is lagging in comparison to Southeast Asian (SEA) neighbors and selected countries in the East Asia and Pacific (EAP) region, as well as aspirational high-income nations. The diagnostic follows the framework of the 2012 World Development Report on Gender Equality and Development, and focuses on three priority areas: human endowments, voice and agency, and economic opportunities. This note also considers the changes in Government and national policies, and on pertinent emerging issues. Malaysia scores poorly in gender-related indicators, although it performs fairly well on a number of human development indicators in international indices. Since the previous Gender Diagnostic Note 2018, Malaysia’s performance in the global gender indices has not changed significantly. For example, in the Women, Business and Law Report 2021, Malaysia maintained its score at 50 and comes in the bottom 20th percentile. When compared to regional comparators and aspirational high-income economies, Malaysia is underperforming.